The Impact Of Child Abuse and Neglect on Oral Habit among 10-11 Years Old Primary School Students in Baghdad /Iraq - Wasan Muwafaq Almirhij1 , Ban Sahib Diab2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The purpose of this study was to assess the impact of child abuse and neglect on oral habits among 10-11 years old primary school students in Baghdad/Iraq. This observational study included 600 studentsdistributed to 373 male and 227 female at different economic and social levels with age 10-11 years old offourth and fifth class of the elementary schools in the Karkh city. Information on child abuse and neglect andpresence or absence of oral habits was obtained from a structured, self-administered questionnaire from thestudents who were willing to participate in the study and their parents. The data was collected, summarizedand statistically analyzed. The child abuse and neglect had effect on presence of oral habits in children.